The CARAMAL study could not assess the effectiveness of rectal artesunate in treating suspected severe malaria - James A. Watson; Thomas J. Peto; Nicholas J. White (BMC Medicine, 2023)
Abstract CARAMAL was a large observational study which recorded mortality in children with suspected severe malaria before and after the roll-out of rectal artesunate in Nigeria, Uganda and the Democratic Republic of the Congo. The results of CARAMAL have had a huge impact on public health policy leading to a World Health Organization moratorium on the roll-out of rectal artesunate. The conclusion reported in the abstract uses strong causal language, stating that “pre-referral RAS [rectal artesunate suppositories] had no beneficial effect on child survival”. We argue that this causal interpretation of the study results is not justified. Data from the CARAMAL study inform chiefly on the strengths and weaknesses of referral systems in these three countries and do not inform reliably as to the beneficial effect of providing access to a known life-saving treatment.